Da escrita para a tela: a produção de documentário como uma prática de ressignificação da escrita no contexto escolar - Azevedo, Judileide Silva Morais de (2021)
The advent of digital technologies and the diversity of multimedia and multisemiotic resources present in communication situations impose on the school the challenge of offering teaching based on real human interaction practices. In this context, we listed as the general objective of this work to present a didactic proposal with the production of the documentary genre, in order to promote a meaningful language teaching that contributes to the identity formation of the subject, problematizing how new technologies, inserted in the school context by through audiovisual language, they can give new meaning to language teaching and bring students closer to the social context in which they live. As specific objectives, we aim to: describe how school writing practices can be re-signified with the help of technological tools; explain how research activities, elaboration of scripts and interviews with people from the neighborhood, in which the school is located, can help students to make a critical reading of their reality; and demonstrate how working with the audiovisual can enable students to use technological tools in favor of building their identity. As for the methodological aspects, this work is configured as an action research from the perspective of Thiollent (1986) and presents a qualitative approach to the data based on the studies by Lüdke and André (2013), because it portrays issues concerning the classroom context. from a didactic proposal structured in a Gender Didactic Project developed by Guimarães and Kersch (2012). Furthermore, our research is based on theoretical contributions by Rojo (2012; 2019) on multiliteracies at school and the contributions of Bauman (2001; 2005) on the formation of the subject's identity. We also support our research in studies that deal with speech genres in the view of Bakhtin (1997); digital genres, according to Marcuschi and Xavier (2005) and social and contemporary literacy based on Kleiman (2014). In the aspects concerning audiovisual language, we base ourselves on the studies by Nichols (2005; 2012). Our didactic proposal was prepared thinking about a possible application in 9th grade classes of elementary school, noting that the production of documentary based on multiliteracies proposals will be important for the construction of meaningful learning in Portuguese language teaching, as it meets the requirements to education in contemporary times.